Expanding the application of tryptophan: Industrial biomanufacturing of tryptophan derivatives - Xiao, Shujian; Wang, Zhen; Wang, Bangxu; Hou, Bo; Cheng, Jie; Bai, Ting; Zhang, Yin; Wang, Wei; Yan, Lixiu; Zhang, Jiamin (Frontiers in Microbiology, 2023)
Tryptophan derivatives are various aromatic compounds produced in the tryptophan metabolic pathway, such as 5-hydroxytryptophan, 5-hydroxytryptamine, melatonin, 7-chloro-tryptophan, 7-bromo-tryptophan, indigo, indirubin, indole-3-acetic acid, violamycin, and dexoyviolacein. They have high added value, widely used in chemical, food, polymer and pharmaceutical industry and play an important role in treating diseases and improving life. At present, most tryptophan derivatives are synthesized by biosynthesis. The biosynthesis method is to combine metabolic engineering with synthetic biology and system biology, and use the tryptophan biosynthesis pathway of Escherichia coli, Corynebacterium glutamicum and other related microorganisms to reconstruct the artificial biosynthesis pathway, and then produce various tryptophan derivatives. In this paper, the characteristics, applications and specific biosynthetic pathways and methods of these derivatives were reviewed, and some strategies to increase the yield of derivatives and reduce the production cost on the basis of biosynthesis were introduced in order to make some contributions to the development of tryptophan derivatives biosynthesis industry.